Child Maltreatment Portrayed in Bangladeshi Newspapers. (31st July 2020) - Atiqul Haque, M.; Janson, Staffan; Moniruzzaman, Syed; Fazlur Rahman, A. K. M.; Islam, Syed Shariful; Mashreky, Saidur Rahman; Eriksson, Ulla‐Britt
Abstract : As in most low‐income countries, there is a lack of scientific information on the incidence and pattern of child maltreatment (CM) in Bangladesh. However, the role of the media to disclose CM and to develop public awareness in society is noteworthy. The present study assessed newspaper reports about CM by type and socio‐demographics of victims and perpetrators in Bangladesh. In total, 790 news articles were collected retrospectively from four Bengali‐ and two English‐language newspapers from October to December 2014. Among all reported incidents, almost half of the CM cases concerned alleged physical abuse (26%) and sexual abuse (22%). Neglect and emotional or psychological abuse received less coverage. Female children were to a high degree (90%) victims of sexual abuse. The main perpetrators were males, and they were often known to the victims. Approximately 32 per cent of the reported abuse cases resulted in death and were related to rape, family violence, administrative negligence, abduction and ransom demand. Some of these deaths were suicides. News stories concerning CM were often reported in an unethical way by identifying the victim and not respecting child rights. Further, the stories seldom discussed the individual or social consequences of CM, or how maltreatment could be prevented. 'The present study assessed newspaper reports about CM by type and socio‐demographics of victims and perpetrators in Bangladesh' Key Practitioner Messages: The main types of reported cases of CM in Bangladeshi print media are physical abuse and sexual abuse, and there is a high proportion of fatal consequences. The perpetrators are often known to the victims. The identity of the victim is frequently reported, potentially putting the child at risk and violating child rights. Bangladeshi print media seldom discusses individual or societal consequences of CM, or how it could be prevented.